Judicial Interpretation of Murābaḥah Contract Restructuring: A Maqāṣid-Based Review of a Palembang Religious Court Case - Muhammad Rohmat Hidayat; Ninik Azizah (Ponpes As-Salafiyyah Asy-Syafi'iyyah, 2025)
The development of Islamic financial institutions in Indonesia has brought new dynamics to the practice of financing contracts, including murābaḥah contracts, which often undergo restructuring due to changing economic conditions. Problems arise when such restructuring leads to legal disputes and is challenged as an act of unlawful conduct. This study analyzes the interpretation of judges at the Palembang Religious Court regarding the restructuring of a murabaḥah contract and assesses its conformity with Muḥammad Ṭahir Ibn ‘Ashur’s theory of maqaṣid al-shari‘ah. This research employs a qualitative method with a normative legal approach through an examination of Decision No. 41/Pdt.G/2021/PA.Palembang, along with sources of Islamic economic law and maqaṣid literature. The findings indicate that the judges interpreted the case legalistically, relying on the principle of pacta sunt servanda and Article 1365 of the Indonesian Civil Code, concluding that the contract restructuring did not constitute an unlawful act. However, from the perspective of Ibn ‘Ashur’s maqāṣid al-shari‘ah, such reasoning does not fully reflect the values of substantive justice (al-‘adl al-ijtima‘i), protection of property (ḥifẓ al-māl), and social welfare (al-maṣlaḥah). Thus, while the court’s decision is formally valid from a juridical standpoint, it has not yet achieved maqāṣid-based justice. Islamic law should be applied by considering its intrinsic spirit of justice to promote social welfare, as envisioned by Ibn ‘Āshūr.